Therapeutic efficacy of unilateral subthalamotomy in Parkinson's disease: results in 89 patients followed for up to 36 months. Issue 9 (9th February 2009) - Alvarez, L; Macias, R; Pavón, N; López, G; Rodríguez-Oroz, M C; Rodríguez, R; Alvarez, M; Pedroso, I; Teijeiro, J; Fernández, R; Casabona, E; Salazar, S; et al.
Abstract : Background: Stereotactic thermocoagulative lesions of the subthalamic nucleus (STN) have been shown to induce significant motor improvement in patients with Parkinson's disease (PD). Patients and methods: 89 patients with PD were treated with unilateral subthalamotomy. 68 patients were available for evaluations after 12 months, 36 at 24 months and 25 at 36 months. Results: The Unified Parkinson's Disease Rating Scale (UPDRS) motor scores improved significantly contralaterally to the lesion in the "off" and "on" states throughout the follow-up, except for the "on" state at the last evaluation. Axial features and signs ipsilateral to the lesion progressed steadily throughout the study. Levodopa daily doses were significantly reduced by 45%, 36% and 28% at 12, 24 and 36 months post-surgery. 14 patients (15%) developed postoperative hemichorea-ballism which required pallidotomy in eight. These 14 patients had significantly higher dyskinesia scores (levodopa induced) preoperatively than the entire cohort. Conclusion: Unilateral subthalamotomy was associated with significant and sustained motor benefit contralateral to the lesion. Further work is needed to ascertain what factors led to severe, persistent chorea-ballism in a subset of patients. Subthalamotomy may be considered an option in circumstances when deep brain stimulation is not viable.